2017
DOI: 10.1177/1060028017710481
|View full text |Cite
|
Sign up to set email alerts
|

SGLT-2 Inhibitors: Is There a Role in Type 1 Diabetes Mellitus Management?

Abstract: A review of the identified literature indicated that there is a potential role for the combination of SGLT-2 inhibitors with insulin in T1DM for improving glycemic control without increasing the risk of hypoglycemia. The short duration and small sample sizes limit the ability to fully evaluate the incidences of diabetic ketoacidosis and urogenital infections. The risks associated with this combination of medications require further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…By inhibiting reabsorption of filtered glucose in the proximal tubule to increase urinary glucose excretion, SGLT2 inhibitors lower blood glucose levels independently of insulin [4]. Therefore, when used alongside insulin, SGLT2 inhibitors offer a means of improving glycaemic control without increasing the risk of insulin-related adverse effects [8]. As SGLT2 inhibitors may improve CV outcomes and bodyweight [9, 10], they may be of particular benefit to patients with high body mass indices (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…By inhibiting reabsorption of filtered glucose in the proximal tubule to increase urinary glucose excretion, SGLT2 inhibitors lower blood glucose levels independently of insulin [4]. Therefore, when used alongside insulin, SGLT2 inhibitors offer a means of improving glycaemic control without increasing the risk of insulin-related adverse effects [8]. As SGLT2 inhibitors may improve CV outcomes and bodyweight [9, 10], they may be of particular benefit to patients with high body mass indices (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…8 Thus, SGLT2 inhibitors alongside insulin may provide a new way, promoting glycaemic control without the increased risk of insulin-related adverse effects. 18 In T2DM patients, SGLT2 inhibitors could lower HbA1c, blood pressure and body weight without increasing major hypoglycaemic events through a non-pancreatic-dependent mechanism of action. 19 Dapagliflozin, an SGLT2 inhibitor, was the first oral treatment approved in T1DM in the European Union, indicating as an adjunct to insulin in adults with T1DM whose BMI of ≥27 kg/m 2 , when insulin alone did not provide adequate glycaemic control despite optimal insulin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, CGM use and data interpretation requires training and experience, has had slow adoption, and its potential remains to be fully realized. Likewise, use of therapies currently approved for the treatment of type 2 diabetes have improved outcomes in T1D such as body weight and insulin dose reductions, insulin sensitization, lowering HbA1c, increasing time in desired glucose range and even reducing glycemic variability; however, most studies have shown responses span the gamut from nonresponders to super-responders [135][136][137][138][139] , thus emphasizing the need for strat-ified, precision medicine approaches. The novel class of SGLT inhibitors, both mono SGLT2 and dual SGLT1/2, are currently in pivotal T1D label expansion studies by manufacturers.…”
Section: Early Stage 3 T1dmentioning
confidence: 99%